LAPAROSCOPIC SPLENECTOMY; SINGLE SURGEON, SINGLE CENTRE INITIAL EXPERIENCE AT TERTIARY LEVEL HOSPITAL IN PESHAWAR - Asim Khan, Muhammad; Kamran, Haider; Ullah, Rafat; Zarin, Mohammad (Journal of Ayub Medical College Abbottabad, 2021)
Background: Despite the fact that Laparoscopic splenectomy has become first choice for most cases of splenectomy in the developed world, open splenectomy is still being done in majority of the developing countries. There is no local data of our hospital on laparoscopic splenectomy. Methods: Cross sectional study of 103 patients with laparoscopic splenectomy from Feb, 2013 to Jan, 2018 done for benign conditions of spleen at Khyber Teaching Hospital, Peshawar. Consecutive non-probability sampling was done. Lateral approach was utilized. Patients’ demographics, preoperative characteristics and intra / postoperative complications were collected on a proforma. Results: Mean age was (26) years. Two third (2/3) of patients were female. Major indication was ITP (Idiopathic Thrombocytopenic Purpura) followed by HS (Hereditary Spherocytosis). Total splenectomy was done in splenic cysts. In half of the cases, platelet and / or blood were transfused preoperatively as a measure of preoperative optimization. Intraoperative & postoperative complications occurred in (8%) which were managed conservatively. Conversion rate was (0%). Triple vaccination was done in almost all patients. Conclusion: Laparoscopic splenectomy is safe in experienced hands and should be the first choice in elective cases even in developing world. Local surgeons should train residents and junior surgeons to improve laparoscopic skills as training abroad is costly.